Spiritual Based Learning Approaches for Addressing Learning Difficulties in Islamic Religious Education: A Qualitative Study in an Indonesian Elementary School - Jusrianti Jusrianti; Amaluddin Amaluddin; Muhammad Naim; Sumadin Sumadin; Dadang Sumarna (CV. Gerasi Insan Nusantara, 2026)
Learning difficulties in Islamic Religious Education (PAI) remain a significant challenge at the elementary school level, particularly in helping students understand faith concepts, perform worship practices, and internalize Islamic values. While previous studies have emphasized cognitive and instructional interventions, limited attention has been given to the role of spiritual-based learning approaches in addressing these challenges. This study aims to examine the implementation of a spiritual approach, evaluate its effectiveness in improving students’ understanding of faith and worship concepts, and identify the supporting and inhibiting factors influencing its application at SD Negeri 64 Buntu Ampang, Anggeraja District, Enrekang Regency, Indonesia. The research employed a qualitative descriptive design using psychological, theological, and pedagogical perspectives. Data were collected through observations, interviews, and documentation involving the principal, Islamic Religious Education teachers, and relevant school stakeholders. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing, while trustworthiness was ensured through triangulation and credibility checks. The findings reveal that the spiritual approach, implemented through prayer, dhikr, Qur’anic recitation, religious motivation, teacher role modeling, and empathetic guidance, effectively supports students in overcoming learning difficulties. The approach contributes not only to improved cognitive understanding of faith and worship but also to enhanced emotional well-being, self-confidence, learning motivation, and positive religious behavior. Its effectiveness is supported by teacher commitment, a strong religious school culture, and institutional support, although limited instructional time, diverse student characteristics, and varying family backgrounds remain challenges. This study highlights the importance of integrating spirituality into classroom practices as a holistic pedagogical strategy for promoting both academic and character development in Islamic Religious Education.